Semiquantitative Strain Elastography of Liver Masses - Onur, Mehmet Ruhi; Poyraz, Ahmet Kursad; Ucak, Esra Ercin; Bozgeyik, Zulkif; Ozercan, Ibrahim Hanifi; Ogur, Erkin (Amer Inst Ultrasound Medicine, 2012)
Objectives-This study was designed to determine the utility of semiquantitative strain elastography in differential diagnosis of solid liver masses. Methods-A total of 103 patients with focal liver masses underwent abdominal sonographic examinations and freehand elastography of focal hepatic lesions. Eighty-two patients (79.7%) with 93 focal hepatic lesions were included in the study. Twenty-one patients (20.3%) were excluded from the study because of technical limitations of semiquantitative strain elastography and difficulty in detection of normal liver parenchyma on gray-scale sonography. We evaluated different focal hepatic lesions such as hemangiomas, focal nodular hyperplasia, nodular regenerative hyperplasia, adenomas, hepatocellular carcinomas, metastases, and cholangiocarcinomas. The stiffness of the lesions was determined by measurement of strain values on semiquantitative strain elastography. The strain index value (strain ratio of liver parenchyma and focal lesions) of each lesion was calculated. Mean strain index values of benign and malignant liver lesions were compared. Results-The mean strain index value of malignant liver lesions +/- SD (2.82 +/- 1.82) was significantly higher than that of benign liver lesions (1.45 +/- 1.28; P<.0001). Hemangiomas had a significantly lower mean strain index value than other benign lesions (P<.0034). There was no statistically significant difference between strain index values of different types of malignant lesions (P>.05). Conclusions-Semiquantitative strain elastography may be helpful for differentiating benign and malignant liver masses. The substantial overlap between strain index values of benign and malignant liver masses limits clinical usefulness of this technique.
Keywords: elastography; liver lesions; sonography; strain in tissue